Explaining the drop of work-hardening rate and limitation of transformation-induced plasticity effect in metastable stainless steels during tensile deformation. (1st July 2023) - Sohrabi, Mohammad Javad; Mirzadeh, Hamed; Sadeghpour, Saeed; Mahmudi, Reza
Abstract: While the occurrence of the transformation-induced plasticity effect in metastable austenitic stainless steels has been adequately explained, the reason behind the fall of work-hardening rate after the maximum value remains largely unknown. In the present work, via extensive work-hardening analysis and examination of the mechanical properties and strengthening mechanisms by the Hollomon analysis, Hall-Petch law, and rule-of-mixtures, it is revealed that the yielding of the deformation-induced martensite leads to the drop of work-hardening rate and limits the strengthening effect of strain-induced martensitic transformation and tensile ductility. Graphical Abstract: Image, graphical abstract